2020
DOI: 10.1093/cid/ciaa879
|View full text |Cite
|
Sign up to set email alerts
|

Use of Baricitinib in Patients With Moderate to Severe Coronavirus Disease 2019

Abstract: Cytokine storm and hyperinflammation are associated with increased mortality in COVID-19. In this small uncontrolled cohort of patients with moderate-severe COVID-19, treatment with baricitinib plus hydroxychloroquine was associated with recovery in 11 of 15 patients. Baricitinib for the treatment of COVID-19 should be further investigated in randomized controlled clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
125
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(131 citation statements)
references
References 12 publications
2
125
2
2
Order By: Relevance
“…Twelve of the 15 patients recovered, and vitals and inflammatory markers were seen to improve after baricitinib was initiated. Two patients however developed serious bacterial or fungal infections due to prolonged ICU stay ( 157 ). A phase III double blind placebo-controlled randomized trial involving baricitinib (NCT04421027) is currently ongoing to assess the efficacy and safety of the drug as a potential immune inhibitor preventing cytokine storm and viral entry.…”
Section: Treatment Protocolsmentioning
confidence: 99%
“…Twelve of the 15 patients recovered, and vitals and inflammatory markers were seen to improve after baricitinib was initiated. Two patients however developed serious bacterial or fungal infections due to prolonged ICU stay ( 157 ). A phase III double blind placebo-controlled randomized trial involving baricitinib (NCT04421027) is currently ongoing to assess the efficacy and safety of the drug as a potential immune inhibitor preventing cytokine storm and viral entry.…”
Section: Treatment Protocolsmentioning
confidence: 99%
“…Nevertheless, no significant relationship was observed between treatment with these two drugs and clinical improvement. 94 According to some reports, baricitinib may lead to anemia, and even, in severe cases, may associate with leukopenia, lymphocytopenia, and thrombocytopenia. Accordingly, a review showed that treatment with baricitinib could lead to anemia in patients with severe COVID-19.…”
Section: Baricitinibmentioning
confidence: 99%
“…In one of the recent pilot study, 12 moderately SARS-CoV-2 infected patients were found to show improvements in clinical and laboratory parameters with baritinicib ( Cantini et al., 2020 ). In another non-controlled, retrospective cohort study with 15 moderate to severe COVID-19 patients, it was reported that baritinicib with HCQ leads to recovery and clinical improvements ( Titanji et al., 2020 ). However, the efficacy of baritinicib could not be confirmed with scant and insufficient clinical results until enough data about the clinical efficiency and safety profile of baricitinib (NCT04321993, NCT04320277) is available.…”
Section: Adjunctive/supportive Care Against Covid-19mentioning
confidence: 99%